Recession and Technological Change: Does Technological Change contribute to Recessions - Aastik Madan (Innovative Research Thoughts, 2023)
This research paper analyses the role of technological change in the occurrence of recessions or periods of strained economic growth. Economists and industry professionals have provided us with various possibilities and causes that lead to the existence of a recession. Even though most economists believe causes such as inflation and unemployment to be the main contributing factors towards the occurrence of recessions, there are some economists, from an alternate school of thought, who attribute the occurrence of recessions to gradual technological change and process innovations. Over the years, there have been multiple research papers published that have tried to establish a correlation between economic growth and technological change. This paper aims to build on this existing research and provide a better and more conclusive explanation for the influence of technological change on the global economy and periods of recession through a detailed analysis of R&D spending, innovations, and employee compositions. The paper will trace the development of the listed aspects through periods of strained economic growth such as the recessions of 2007-2009 and 1991-92 to establish an effective line of reasoning.